1997
DOI: 10.1007/bf02062030
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-filling procedure for transsphincteric fistulas

Abstract: The muscle-filling technique is an effective alternative procedure for transsphincteric fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…9 The results obtained in the present study compare favorably with other studies in the treatment of posterior transsphincteric fistulas, with a 4.6 percent recurrence rate during a mean follow-up of 70 months. Iwadare et al 6 reported personal experience with a 1.5 percent recurrence rate. Recently, the results of sphincter-preserving procedures in Japan have a 7 to 10 percent recurrence rate for transsphincteric fistulas.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…9 The results obtained in the present study compare favorably with other studies in the treatment of posterior transsphincteric fistulas, with a 4.6 percent recurrence rate during a mean follow-up of 70 months. Iwadare et al 6 reported personal experience with a 1.5 percent recurrence rate. Recently, the results of sphincter-preserving procedures in Japan have a 7 to 10 percent recurrence rate for transsphincteric fistulas.…”
Section: Discussionmentioning
confidence: 96%
“…It also reduces the recurrence rate. 6,7 Even though the technique requires cutting the external and internal sphincters appropriately to make a pedicle muscle flap, proponents of the muscle-filling procedure believe the damage to the sphincter is far less than in other procedures, and the damage to the internal sphincter is virtually negligible, whereas opponents argue that the technique could produce unnecessary damage to the external sphincter. We think that because the dead space left by excision of the primary abscess is quite deep, it requires a wider wound for appropriate drainage, which would sacrifice more of the external sphincter.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Various techniques have been reported in the literature with varying success. [2][3][4][5] This technical note illustrates a new technique that uses a distal portion of the anal sphincters and subcutaneous fat as an advancement flap to cover the internal opening of low transsphincteric fistulas.…”
mentioning
confidence: 99%